Pengaruh Motivasi Intrinsik dan Ekstrinsik Terhadap Prestasi Belajar Siswa Mata Pelajaran Bahasa Arab Kelas V di MI Al Azkia Tenjolaya Bogor - Linda Urfatullaila; Ima Rahmawati; Zulfikar Ismail (Prodi PGMI IAI Sahid, 2022)
The aim of this research is to determine the influence of intrinsic and extrinsic motivation on the learning achievement of students in class V Arabic at MI Al Azkia Tenjolaya Bogor. This research uses a quantitative approach with a sample of 39 respondents using non-probability sampling techniques with a saturated sample. Data collection uses questionnaires, non-participant observation and documentation. The data analysis technique used is multiple linear regression using the SPSS 20.0 application. Based on the results of the multiple linear regression test, Fcount (11.247) > Ftable (3.26) and a significant value of 0.000 <0.05, it can be concluded that there is a positive and significant influence between intrinsic and extrinsic motivation together on learning achievement. This shows that the stronger the influence of intrinsic and extrinsic motivation together, the greater the learning achievement produced by students.